Antigen receptor‐engineered Tregs inhibit CNS autoimmunity in cell therapy using nonredundant immune mechanisms in mice. Issue 8 (27th May 2022) - Pohar, Jelka; O'Connor, Richard; Manfroi, Benoît; El‐Behi, Mohamed; Jouneau, Luc; Boudinot, Pierre; Bunse, Mario; Uckert, Wolfgang; Luka, Marine; Ménager, Mickael; Liblau, Roland; Anderton, Stephen M.; et al.
Abstract: CD4 + FOXP3 + Tregs are currently explored to develop cell therapies against immune‐mediated disorders, with an increasing focus on antigen receptor‐engineered Tregs. Deciphering their mode of action is necessary to identify the strengths and limits of this approach. Here, we addressed this issue in an autoimmune disease of the CNS, EAE. Following disease induction, autoreactive Tregs upregulated LAG‐3 and CTLA‐4 in LNs, while IL‐10 and amphiregulin (AREG) were increased in CNS Tregs. Using genetic approaches, we demonstrated that IL‐10, CTLA‐4, and LAG‐3 were nonredundantly required for the protective function of antigen receptor‐engineered Tregs against EAE in cell therapy whereas AREG was dispensable. Treg‐derived IL‐10 and CTLA‐4 were both required to suppress acute autoreactive CD4 + T‐cell activation, which correlated with disease control. These molecules also affected the accumulation in the recipients of engineered Tregs themselves, underlying complex roles for these molecules. Noteworthy, despite the persistence of the transferred Tregs and their protective effect, autoreactive T cells eventually accumulated in the spleen of treated mice. In conclusion, this study highlights the remarkable power of antigen receptor‐engineered Tregs to appropriately provide multiple suppressive factors nonredundantly necessary to prevent autoimmune attacks. Abstract : Graphical Abstract: Autoreactive Tregs produced by gene therapy are a promising approach for cell therapy of immunological diseases. We found that IL‐10, CTLA‐4, and LAG‐3 were nonredundantly involved in their protective effect in EAE, underlining their unique capacity to appropriately deliver in time and space crucial nonredundant mechanisms of immune regulation.